2013
DOI: 10.1136/annrheumdis-2012-202481
|View full text |Cite
|
Sign up to set email alerts
|

Using lifestyle factors to identify individuals at higher risk of inflammatory polyarthritis (results from the European Prospective Investigation of Cancer-Norfolk and the Norfolk Arthritis Register—the EPIC-2-NOAR Study)

Abstract: ObjectivesTo investigate the association of lifestyle factors with risk of inflammatory polyarthritis (IP) and rheumatoid arthritis (RA).MethodsThe European Prospective Investigation of Cancer, Norfolk, UK (EPIC-Norfolk) gathered lifestyle data from participants aged 40–79 years from 1993 to 1997. Individuals who subsequently developed IP were identified by linkage with the Norfolk Arthritis Register. A Cox proportional hazard model was developed, and a score assigned to each risk factor to calculate the odds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 52 publications
7
88
0
3
Order By: Relevance
“…Based on earlier research related to chronic diseases included in this study, serum cholesterol is associated strongly only with CVD whereas smoking as well as obesity are known risk factors for most of the chronic conditions included in analyses [18][19][20][21][22][30][31][32] explaining also the weak predictive effect seen for serum cholesterol in this study. In additions, after our 10-year follow-up the oldest participants were only 74 years old, which nowadays is a relatively low age for CVD event especially among women in Finland [33].…”
Section: Discussionmentioning
confidence: 82%
“…Based on earlier research related to chronic diseases included in this study, serum cholesterol is associated strongly only with CVD whereas smoking as well as obesity are known risk factors for most of the chronic conditions included in analyses [18][19][20][21][22][30][31][32] explaining also the weak predictive effect seen for serum cholesterol in this study. In additions, after our 10-year follow-up the oldest participants were only 74 years old, which nowadays is a relatively low age for CVD event especially among women in Finland [33].…”
Section: Discussionmentioning
confidence: 82%
“…Two case-control studies including 515 recent RA with 769 controls and 2748 RA with 3444 controls discovered a positive association between obesity and likelihood of developing RA negative for ACCP, with an increased risk of 3.45 (1.73 to 6.87) in the first study and 1.6 (1.2 to 2.2) in women in the second study. 33,38,39 Similarly, in two cohort studies performed by Lahiri et al and Lu et al large number of patients with RA were studied and monitored for a long term, they found that obesity is linked to high incidence of seronegative inflammatory polyarthritis (HR 2.75; 95% CI 1.39 to 5.46) 40 and seronegative RA (HR 1.34; 95% CI 1.03 to 1.74) 41,33 respectively. Furthermore, in the Lu et al study, the risk for patients with obesity who develop RA with onset before 55 years was much more increased in all patients with RA (seropositive and seronegative) (HR 1.65; 95% CI 1.34 to 2.05).…”
Section: Resultsmentioning
confidence: 91%
“…45 A 2014 prospective population study also demonstrated that both diabetes mellitus and obesity were risk factors for the development of inflam matory polyarthritis. 46 All three conditions (diabetes mel litus, obesity and RA) are known to be associated with chronic inflammation and increased levels of circulating adipokines, which might influence the initiation and course of both CVD and RA.…”
Section: Traditional Cardiovascular Risk Factorsmentioning
confidence: 99%